2020
DOI: 10.1097/crd.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Testosterone in Patients With Heart Failure: A Systematic Review

Abstract: The consequences of heart failure (HF) remain high despite treatment advances. Deficiency of the anabolic axes is common in HF and is associated with an increased risk of death and worsening functional status. Exogenous testosterone use has been shown to decrease vascular resistance and improve cardiac output. The objective of this systematic review was to assess the efficacy (mortality, hospitalization, cardiac function, and quality of life) and safety of testosterone in HF patients. The Preferred Reporting I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In general, MACE-related signals generated by TT were stronger than those generated by TD, but were weaker than their counterparts generated by patients with DM and hypertension. These findings indicated that TT may improve the cardiac output, as suggested by previous publications ( Pugh et al, 2004 ; Park et al, 2021 ), potentially benefiting ischemic myopathy. However, it may have a negative impact on cardiac failure caused by congestive reasons, indicating that the effects of testosterone on the heart are complex and context-dependent; while it seems to have no significant effect on cardiac arrhythmia-related MACEs, although animal models suggest that androgen increases the risk of hydro-electrolytic and autonomic imbalances, but did not alter the vascular or cardiac function or morphology ( Salimi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 84%
“…In general, MACE-related signals generated by TT were stronger than those generated by TD, but were weaker than their counterparts generated by patients with DM and hypertension. These findings indicated that TT may improve the cardiac output, as suggested by previous publications ( Pugh et al, 2004 ; Park et al, 2021 ), potentially benefiting ischemic myopathy. However, it may have a negative impact on cardiac failure caused by congestive reasons, indicating that the effects of testosterone on the heart are complex and context-dependent; while it seems to have no significant effect on cardiac arrhythmia-related MACEs, although animal models suggest that androgen increases the risk of hydro-electrolytic and autonomic imbalances, but did not alter the vascular or cardiac function or morphology ( Salimi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 84%
“…A big systematic review including 10 randomized controlled trials showed TTh in patients with heart failure (HF) was not associated with an increase in mortality or HF hospitalization rate [167]. Moreover, Oni et al demonstrated in a large observational cohort of male veterans with previous myocardial infarction (MI), normalization of TT levels with TTh was associated with decreased all-cause mortality compared with those with non-normalized TT levels and the untreated group.…”
Section: Recommendation 10: Testosterone Cardiovascular Disease and All-cause Mortalitymentioning
confidence: 99%
“…Recently, particular attention has been focused on HF patients. In this group, testosterone supplementation is considered as an additional way of pharmacological treatment to improve cardiac health, but the results are still inconclusive, even with reported possible deterioration of heart function (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%